2016
DOI: 10.1371/journal.pone.0158807
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in Adverse Pregnancy Outcomes - A Retrospective Australian Population Study 1981-2011

Abstract: ObjectivesSexual inequality starts in utero. The contribution of biological sex to the developmental origins of health and disease is increasingly recognized. The aim of this study was to assess and interpret sexual dimorphisms for three major adverse pregnancy outcomes which affect the health of the neonate, child and potentially adult.MethodsRetrospective population-based study of 574,358 South Australian singleton live births during 1981–2011. The incidence of three major adverse pregnancy outcomes [preterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 40 publications
6
61
0
1
Order By: Relevance
“…Furthermore, Cordero et al identified 117 miRNAs present in buffy coat samples, which were differentially methylated between men and women [90], some of which overlap with the cord blood miRNAs identified in our study. It is possible that differences in oxidative stress, inflammation, growth and birth outcomes observed between newborn boys and girls [91][92][93] could be controlled, at least in part, by differentially expressed miRNAs. Age is another host factor that can bias epigenetic markers [94,95].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cordero et al identified 117 miRNAs present in buffy coat samples, which were differentially methylated between men and women [90], some of which overlap with the cord blood miRNAs identified in our study. It is possible that differences in oxidative stress, inflammation, growth and birth outcomes observed between newborn boys and girls [91][92][93] could be controlled, at least in part, by differentially expressed miRNAs. Age is another host factor that can bias epigenetic markers [94,95].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the large number of births in this cohort available for assessment adds to the study strength, enabling identification of over 1,300 women with kidney disorders, and with disease subgroups in sufficient numbers for novel comparative analysis. The POU database has previously been extensively utilized as a research database providing high-quality population-level data [32][33][34]; however, the limitations of diagnostic coding data are acknowledged. ICD-9 codes rather than ICD-10 are captured in this dataset.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we examined the extent to which the association of wGRS with AP risk is modified by known and potential risk factors of AP: preeclampsia, 32 advanced maternal age, 33 and infant sex. 34 These analyses could have important clinical and public health implications by highlighting potential gene-gene or gene-environment interactions, enhancing the biologic understanding of the mechanisms that lead to AP, and facilitating therapeutic efforts to reduce impact of AP. 35 …”
Section: Introductionmentioning
confidence: 99%